KINERJA AGRIBISNIS SAPI POTONG RAKYAT DI PROVINSI JAWA TIMUR: DAMPAK KRISIS MONETER DAN IMPLEMENTASI KEBIJAKAN OTONOMI DAERAH - HENNY MAYROWANI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2006)
In the period of 1995 - 2002, domestic cattle agribusiness in East Java has indicated anunpleasant condition, the growth of production, consumption and trade tend to decreasearound 1.5 - 4.7 percent a year. Meanwhile, nominal price of feed and livestock productshave increased more than 8 percent. Although, the real prices were increasing only around0.5 - 1.4 percent a year. Economic crisis affect significantly the decreasing of thehousehold income, it has an impact in reducing of the volume of East Java cattledistribution to outer region. This condition become worse by reduction of cattle populationgrowth and competition with live cattle import and their products. In 1995-2002 and duringthe regional autonomy policy implementation process, cattle population growth hasdecreased - 1.71 and - 24.85 percent a year respectively. Generally, decreasing of cattlepopulation growth has related to reduction of cattle herd that no longer used inintensification of paddy field. Decreasing of cattle population growth during the regionalautonomy policy implementation process were caused by three reasons, such as: (1) Lackof local government ability to increase the development of breeding and fattening businessthat related to the budget and government management problems; (2) Market demand ofcattle from outer region was decreasing; and (3) The real price of breed and fattening cattlewas not attractive for farmers to carry on in their business. Based on those problemsabove, in order to develop domestic cattle agribusiness, it is necessary to develop: (1) Thepolicy which able to consolidate the central, province, and district government inimplementing integration programs; (2) Reducing market distortion policies; (3) Provideprotection and special treatment for small scale farmers to face global trade liberalization;and (4) Institutional reform of domestic cattle agribusiness.